Understanding the Landscape of Usability Evaluation in Geographic Information Systems: A Systematic Literature Review - Kurniawan, Dedy; Rosa Indah, Dwi; Sari, Purwita; Alif, Rahmat (Journal of Applied Science, Engineering, Technology, and Education, 2023)
This systematic literature review comprehensively examines usability evaluation in Geographic Information Systems (GIS). The study explores the importance of usability evaluation, common usability issues, and the role of usability evaluations in GIS design and development. The review reveals a critical need for more scientific publications of up-to-date GIS usability evaluations. It highlights the importance of usability evaluations in developing more user-friendly GIS applications. The findings underscore the need for improved user guidance and more intuitive design of GIS applications, particularly for novice users. The review also identifies several opportunities for future research, including developing usability guidelines for GIS, exploring new methods for analyzing GIS interactions and workflows, and considering GIS use over more extended periods. The findings have significant implications for GIS developers, users, and researchers, emphasizing the importance of conducting usability evaluations to enhance user satisfaction and improve task performance.